2016
DOI: 10.1080/00325899.2016.1148847
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening behaviour and mechanisms of extruded powder metallurgy pure Ti materials reinforced with ubiquitous light elements

Abstract: Ubiquitous light elements (ULEs) like oxygen (O), nitrogen (N), carbon (C) and hydrogen (H) can be the key additive elements to achieve the high specific strength and cost-effectiveness of powder metallurgy (PM) titanium (Ti) materials. They have high potential to be employed as promising useful reinforcements of conventional expensive alloying elements like vanadium (V) and Niobium (Nb). In this study, two ULEs, oxygen and hydrogen, were induced into pure Ti matrix via the PM route, and then the processed Ti … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 17 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…The homogeneous fine-grained structure resulting from severe plastic deformation typically decreases the ductility of a metal [11,[14][15][16][17][18], including that of CP titanium [11,14,15], via the early induction of plastic instability. Previous investigations have demonstrated that a new microstructural design can improve both the strength and ductility (or toughness) of some metallic materials [8,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. As an example, Sergueeva et al [8] reported that both the strength and elongation of CP titanium were improved by high-pressure torsion followed by brief low temperature annealing.…”
Section: Introductionmentioning
confidence: 99%
“…The homogeneous fine-grained structure resulting from severe plastic deformation typically decreases the ductility of a metal [11,[14][15][16][17][18], including that of CP titanium [11,14,15], via the early induction of plastic instability. Previous investigations have demonstrated that a new microstructural design can improve both the strength and ductility (or toughness) of some metallic materials [8,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. As an example, Sergueeva et al [8] reported that both the strength and elongation of CP titanium were improved by high-pressure torsion followed by brief low temperature annealing.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 4) reported that pure copper with a bimodal grain size distribution created by a thermo-mechanical treatment exhibited stable tensile deformation leading to a high tensile ductility. Kondo et al 7), 8) reported that pure titanium with high strength and high elongation was fabricated by the elemental mixtures of TiH2 and TiO2 powders in solid state. The author's group 9)-15) has developed an exquisite microstructural design, called "harmonic structure", which consists of the coarse-grained structure surrounded by the network structure with fine grains.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, recent developments have suggested that these interstitial elements can be used to significantly improve the tensile properties of PM Ti alloys. Figure 7 shows the excellent tensile properties of Ti containing light elements up to 1.66 wt% O, 0.90 wt% N, and 0.33 wt% H. [97][98][99]101,[104][105][106][107]118] For example, Ti-1.66 wt% O alloy achieved UTS ¼ 1378 MPa, YS ¼ 1213 MPa, and tensile elongation ¼ 18.1% [104] ; Ti-0.479 wt% N alloy exhibited UTS ¼ 1146 MPa, YS ¼ 1045 MPa, and tensile elongation ¼ 11%, [101,107] and Ti-0.33 wt% H delivered UTS %960 MPa, YS %800 MPa, and tensile elongation ¼ 27.5%. [99] Hybrid reinforcement by N þ H, O þ N, or O þ H also showed encouraging results.…”
Section: Novel Timmcs Reinforced With O N and Hmentioning
confidence: 99%
“…[99] Hybrid reinforcement by N þ H, O þ N, or O þ H also showed encouraging results. [105,106,115] For instance, Ti-0.97 wt% O-0.11 wt% H, and Ti-0.6 wt% N-0.07 wt% H showed UTS ¼ 1158 MPa, YS ¼ 990 MPa, elongation ¼ 23.9%, [105] and UTS ¼ 1047 MPa, YS ¼ 918 MPa, elongation ¼ 16.6%, [106] respectively. All these property combinations are superior to these of mill-annealed Ti-6Al-4V.…”
Section: Novel Timmcs Reinforced With O N and Hmentioning
confidence: 99%